The Relationship Between Nutritionist Support and Dietary Compliance Among Pregnant Women with Anemia - Tutik Ekasari; Maya Erisna (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2026)
Nutritionist support during pregnancy plays an important role in improving dietary compliance among pregnant women with anemia. Adequate dietary adherence is essential to maintain maternal nutritional status and prevent complications associated with anemia during pregnancy. This study aimed to determine the relationship between nutritionist support and dietary compliance among pregnant women with anemia. This research used an analytical observational design with a cross-sectional approach. The study involved pregnant women with anemia who attended antenatal care services at a selected health center method (purposive sampling N=41). Nutritionist support was measured using a structured questionnaire covering education, counseling, motivation, and monitoring aspects, while dietary compliance was assessed using a dietary adherence questionnaire. Data were analyzed using the Spearman correlation test with a significance level of p<0.05. The results showed that most respondents who received good nutritionist support demonstrated higher dietary compliance compared to those who received less support. Statistical analysis indicated a significant relationship between nutritionist support and dietary compliance among pregnant women with anemia (p<0.05), where better nutritionist support was associated with improved dietary adherence. These findings suggest that strengthening nutrition counseling and continuous support from nutritionists may improve dietary compliance and help reduce the risk of anemia-related complications during pregnancy.